Investigating usage and constraints of green outdoor environment at workplaces in Kuala Lumpur, Malaysia - Siba, Maria Arlene Jackan (2020)
Green outdoor environment (GOE) is a dynamic infrastructure to an urban area and part of the city’s ecosystem. Although numerous studies have been carried out on GOE, there is still lacking of information on GOE and its relationship in term of benefits and usability by office employees. Whilst Kuala Lumpur has many different types of urban green space, this study focused on the use and preferences of selected five GOE within 0-1km from workplaces in Kuala Lumpur city centre zone (CCZ) and survey conducted among N=326 respondents consisting of office employees within the area. This study presented results on an extensive scope of GOE-related issues at the workplace and visits to the Kuala Lumpur CCZ office employees. It provided details on the characteristics of the visitors, what motivates them to visit (or not visit) and what they do once there, the duration of their stay and what they see as important attributes in terms of being able to spend time at GOE and the satisfaction of the overall quality of GOE. This study also allows GOE at workplaces in the Kuala Lumpur CCZ to be developed according to the visitors perspectives and meeting the needs of its visitors. The respondents relate their concerns about the location of GOE at workplaces in the Kuala Lumpur CCZ, accessibility, quality of the environment and other personal issues like hectic working hours and health issues. By determining the function of GOE, we can identify any potential of GOE in Malaysian context despite its small size and maximise the use of GOE in the Kuala Lumpur CCZ as an urban space that can provide green, healthy, inclusive, open and public spaces for the citizen of Kuala Lumpur.